Mythic of Newar Arts, Literature, Tales, Oral Histories and Rituals in Patan and Kritipur: Cultural Study - Gautam, Mani Bhadra (Pragya Darshan प्रज्ञा दर्शन, 2023)
Mythic realities in Newar arts and cultural representations of the socio-cultural activities noted in the folklores, tales, practices and performances in Patan and Kirtipur are mysteries. Ritual activities like Lakhe Dances, Jatras and other rituals are related with the historical events, facts and imaginary-mysterious beliefs. Myth is an excavating tool for meaning making of the artistic, cultural and historical sayings noted in the tales that can catch out the themes observing the coverage of crafts in applying the artistic and literary techniques. Newar Arts, Newa Dance, Dhime Dance, Lakhe Dance and other magical activities and rituals of Patan and Kirtipur are culturally connected with mythic realities of folklores. The cultural study helps to study the arts, culture and literature and myth making in creating the meanings through library and internet-based resources and it is also prepared on the basis of field visit reports and therefore this study applies both the qualitative and quantitative approaches. Objective of this article is to expose the mythical images and it analyzes present events in field-based method studying the human emotions, feelings and their cultural practices. It also investigates on the subjects of religious activities, socio-cultural practices and cultural representations of the past reality and present changes in a different way. This article presents a brief sketch of a new perspective on cultural orientation to mythical world as myth and mystery reflecting on the past activities and creating the meanings in the present. Cultural study is one of the tools to excavate Patan and Kirtipur’s history and so in this article Stuart Hall’s ideas are applicable.